The Impact of Reading Habit of Jakarta Post Towards Students’ Linguistic Features - Waskito, Syifa Aulia Putri; Sudar, Sudar; Chasanah, Zulia (Scripta : English Department Journal, 2024)
The purpose of this research aims to determine the student’s reading habits of Jakarta Post, their linguistic features of comprehension focusing on words and morphemes, and the impact of these habits on their linguistic features of comprehension focusing on words and morphemes. A mixed method was used in this research. The statistical population of this study was 45 students from the third semester of English language education. The sample of this research class B was 20 students.The result of the research revealed that the mean scores of pre-tests was 71.95, while the mean scores of post-tests was 83. The result of the two-sided significance value is 0.000. Compared to the significance level of 5% (0.05), the statistic shows that the two-fold significance level is lower than the significance level of 5% (0.00 < 0.05). In addition, the results of the interview also showed that students had a good answer about reading habit of Jakarta Post. This study’s result indicated that reading habit of Jakarta Post has a significant effect. It positively impacts students’ linguistic features comprehension, focusing on word & morpheme.